A single nanowire sensor for intracellular glucose detection. Issue 22 (29th May 2019) - Liao, Quan-Lan; Jiang, Hong; Zhang, Xin-Wei; Qiu, Quan-Fa; Tang, Yun; Yang, Xiao-Ke; Liu, Yan-Ling; Huang, Wei-Hua
Abstract : We report for the first time the development of a single nanowire electrochemical sensor for the detection of intracellular glucose levels. Abstract : Glucose metabolism plays an important role in cell energy supply, and quantitative detection of the intracellular glucose level is particularly important for understanding many physiological processes. Glucose electrochemical sensors are widely used for blood and extracellular glucose detection. However, intracellular glucose detection cannot be achieved by these sensors owing to their large size and consequent low spatial resolution. Herein, we developed a single nanowire glucose sensor for electrochemical detection of intracellular glucose by depositing Pt nanoparticles (Pt NPs) on a SiC@C nanowire and further immobilizing glucose oxidase (GOD) thereon. Glucose was converted by GOD to an electroactive product H2 O2 which was further electro-catalyzed by Pt NPs. The glucose nanowire sensor is endowed with a high sensitivity, high spatial-temporal resolution and enzyme specificity due to its nanoscale size and enzymatic reaction. This allows the real-time monitoring of the intracellular glucose level, and the increase of the intracellular glucose level induced by a novel potential hypoglycemic agent, reinforcing its potential application in lowering the blood glucose level. This work provides a versatile method for the construction of enzyme-modified nanosensors to electrochemically detect intracellular non-electroactive molecules, which is of great benefit for physiological and pathological studies.